The Idea of Freedom in Radical and Delibe-rative Models of Democracy - UFEL, WOJCIECH (Journal of Education Culture and Society, 2020)
Basing on the idea of freedom brought by I. Berlin we can derive to classical models of democracy: liberal and republican. Refl ection on postmodern theories of democracy – radi-cally plural and deliberative – points that they do not strongly differ from the traditional ones, but rather give them new challenges. Radical democracy of Ch. Mouffe and E. Laclau praising pluralism and negative freedom is a deconstruction of a liberal model, while delib-erative project of J. Habermas, praising community and negative freedom, remains in a republican tradition. In the end of the article the author also presents the understanding of the educative role of society and tradition in both classical and postmodern models of democracy.